THE RELATIONSHIP BETWEEN STUDENTS’ VOCABULARY KNOWLEDGE AND THEIR SPEAKING ABILITY - Roswati Roswati; Destri Wahyuningsih; Batdal Niati; Fiska Ardiawati; Fajar Wirawan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The purpose of this research is to find out if there is significant relationship between students’ vocabulary knowledge and their speaking ability. The method used in this research is a correlation design which has two variables, variable X (vocabulary knowledge) and variable Y (speaking ability). The populations of this research were 275 of the second-grade students of MTs Darul Hikmah Pekanbaru and the researcher take 28 students as the sample. The researcher employed Simple Random Sampling technique. In collecting data, the researcher distributed objective test and take an oral test. The researcher analyzed the data with Pearson Product Moment Correlation formula by using SPSS 23.0 version. The results of this research, students' vocabulary knowledge has an average score of 73.04, which is categorized as